2017
DOI: 10.21608/jenvbs.2017.1089.1006
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application: from plant nutrition to biofortification

Abstract: IT is well known that, sustainable agriculture is an important part of sustainable development. This sustainable agriculture should lead to achieve food security and maintain the biodiversity of natural ecosystems. Sustainable agriculture also should have definitely a global perspective. The conservation of both soil and water resources, therefore, is considered an essential prerequisite as well as the efficient use of mineral and organic fertilizers. This could be achieved by improving agro-technology and bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 61 publications
0
59
0
3
Order By: Relevance
“…However, seedlings on the Gelrite® culture showed severe symptoms of senescence from the third week onwards and died after 4-5 weeks ( Figure 1D). Although this medium resulted in fast seed germination, it proved detrimental to seedling development, as the lack of essential nutrients prevents plants completing their life cycle (Taiz et al, 2015;Alshaal and El-Ramady, 2017). Koné et al (2015) also reported the lowest growth performance of V. subterreana seedlings grown on a control medium without inorganic salts.…”
Section: Seedlings Derived From Seeds Germinated Directly On Gelrite®mentioning
confidence: 99%
“…However, seedlings on the Gelrite® culture showed severe symptoms of senescence from the third week onwards and died after 4-5 weeks ( Figure 1D). Although this medium resulted in fast seed germination, it proved detrimental to seedling development, as the lack of essential nutrients prevents plants completing their life cycle (Taiz et al, 2015;Alshaal and El-Ramady, 2017). Koné et al (2015) also reported the lowest growth performance of V. subterreana seedlings grown on a control medium without inorganic salts.…”
Section: Seedlings Derived From Seeds Germinated Directly On Gelrite®mentioning
confidence: 99%
“…It is affected by endogenous (leaf anatomy), exogenous (pH, soil), as well as environmental factors. After foliar Fe application, it takes the plants 10–20 days to absorb 50% of the micronutrient (Alshall and El-Ramady, 2017). In contrast with the promising results of foliar fertilizer application to improve grain Zn in rice (Cakmak, 2008; Cakmak and Kutman, 2017), the increase of grain Fe using foliar fortification was modest.…”
Section: Biofortification: Agronomic Vs/and Genetic In Rice and Wheatmentioning
confidence: 99%
“…Bioavailable biogenic elemental Se (BioSe), for example, is widespread in the microbial environment ( Winkel et al, 2012 ). For roles in foliar biofortification, Se and I nanoparticles need to be well characterised, including particle size: stomatal openings are about 20 nm in diameter, thus movement of particles larger than this is problematic ( Alshaal and El-Ramady, 2017 ).…”
Section: Biofortification Of Cereals With Selenium and Iodine Could Rmentioning
confidence: 99%